The three month's dietary brown rice intervention has not significantly decreased levels of CRP, TNF- α, and IL6 of type 2 diabetes mellitus patients - Fajar Ari Nugroho; Inggita Kusumastuty; Anggun Rindang Cempaka; Atifa Nafia Hasantie Latif; Dian Handayani (PAGEPress Publications, 2023)
Introduction: The increased quantities of inflammatory biomarkers such as C-Reactive Proteins (CRP), Tumour Necrosis Factor-α (TNF-α), and Interleukin-6 (IL-6) have been reported to be associated with an increased risk of metabolic syndrome including type 2 diabetes mellitus (T2DM). However, brown rice is an alternative dietary food source that is known to have many health benefits including high fibre content. In addition to fibre, brown rice is also reported to have moderate amounts of proteins, unsaturated lipids, several minerals, and a lot of bioactive substances that are highly beneficial to health. This study aims to prove the role of brown rice dietary intervention in the reduction of inflammatory biomarkers in type 2 diabetes mellitus patients. Design and Methods: This was a cross-sectional study with a post-test conducted on 18 patients with type 2 diabetes mellitus. In the intervention phase I, all type 2 diabetes mellitus patients were given brown rice diet for 3 months and followed by a phase II intervention, in which white rice diet was given to the other group of type 2 diabetes mellitus patients for 3 months. Serum was collected at the end of each intervention stage and then serum for Tumour Necrosis Factor-α, Interleukin-6 and C-Reactive Proteins were analysed by the ELISA method. Statistical analysis of the t-test was conducted in order to determine the differences between the two groups allocated in the study. Results: At the end of the study, it was found that the levels of C-Reactive Protein, Tumour Necrosis Factor-α, and Interleukin-6 after the brown rice intervention was given to type 2 diabetes mellitus patients, it showed a decreasing trend compared to the white rice intervention although not significantly different (p = 0.6, p = 0.63, p = 0.59, respectively). Conclusions: This study concluded that the administration of brown rice dietary intervention to patients with type 2 diabetes mellitus for 3 months was able to reduce Tumour Necrosis Factor-α, C-Reactive Proteins, and Interleukin-6 however, the reduction was not significant to influence policy change.